The Gender Inequality in Education and Employment: A Study in India - Gogoi, Purabi; Hazarika, Mahendra; Gogoi, Manuranjan (INTERNATIONAL JOURNAL OF ECONOMICS AND MANAGEMENT REVIEW, 2025)
Purpose - This paper is an attempt to study the gender gap in access to education and employment in India. By collecting data on various education and employment indicators from NSS reports and Periodic Labourforce Survey data. Design/methodology/approach - The study is based on secondary data collected from various sources including- Periodic Labouforce Survey data, Ministry of Statistics and Programme Implementation, Govt. of India, reports of UNDP, reports of NSSO, Reports of Ministry of Education, published journal articles, books etc. Findings and Discussion - This paper is an attempt to study the gender gap in access to education and employment in India. By collecting data on various education and employment indicators from NSS reports and Periodic Labourforce Survey data, the study found that there exists a huge gender gap in access to employment opportunities and in education also. It necessitates the government to search some other underlying causes of gender gap in India in general and in education and employment in particular. Lack of access to education by female compared to male is not only the cause of less access to labour market by female. The study also added that social norms, customs, women’s traditional role, people’s attitude towards education are also related factors for gender gap in labour market. Conclusion - The paper attempts to study about the gender gap in education and employment in India. And it has found that in India, females have less access to both education and employment. There was slight improvement in access to education by female particularly in 2018-19 which may be due to the implementation of Samagra Shiksha in India.